PENYULINGAN AIR BERSIH UNTUK MENINGKATKAN KUALITAS AIR BERSIH DI MUARA FAJAR BARAT - Sukri Sukri; Fitra Ramdhani; Rizki Ramadhan Husaini; Siti Juariah (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Clean water is a need that must be met for everyday, both individual needs and the needs of household groups. The quality of water that is needed everyday is colorless, no smell and dirty, the village of estuary in the middle of the morning is an area close to oil wells and highlands that have very low levels of water cleanliness. Muara Fajar Barat village has high iron content so that it cannot be used for consumption and even for bathing. The West Dawn Estuary community must buy water for daily needs with costs incurred every 3 days reaching 50000 rupiah or an average of 13,000 every day. The economic conditions of the underprivileged people are added to the economic burden with daily expenses by issuing the clean water financing. With this condition there needs to be a solution offered in order to reduce economic burdens and environmental friendliness, for that we need an innovative water purifier tool with a distillation method using natural ingredients and a paralon pipe as a wrapper. The water filter that is made can meet the needs of every daily household by spending only 100,000 euros every 2 months. The decline in the burden of the eastern dawn estuary community could reach 140000 rupiahs every 2 months or 70000 rupiahs